Pengaruh Variasi Sudut Water Injector Berbentuk Diffuser Terhadap Fenomena Flooding Pada Aliran Dua Fase Cair – Udara Vertikal Berlawanan Arah - Budiprasojo, Azamataufiq; Soenoko, Rudy; Wahyudi, Slamet (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Flooding phenomenon becomes a looses in countercurrent two-phase flow of air-liquid in vertical pipe. Water injector sattached in to the pipe prevents the looses occur. With the use of water injector, liquid will flow attached to the inside wall of the pipe, so the air will flow freely in the middle of the pipe. New design of water injectors in diffuser shape, will be studied to replace the old annular water injectors. 10 o , 15 o , and 20 o of water injector angle will be varied to find which ones can make slowing down flooding. This Research will seek water injectors with the most slowing down flooding, indicating by it superficial velocity, fluid flow, and flow patterns. Abetter Water injector is in whis have ability to handle higher flow rate and higher superficial velocity. The best water injectors in a row is a water injector with 10 o , 20 of angle.Keywords : two phase, counter current flow, flooding, water injector, flow pattern.